Economic Growth, Renewable Energy Consumption, Financial Development, and Ecological Sustainability in European Union Countries: Does Digital Economy Matter? (Innovations in Environmental Economics, 2025)
This study explores the role of economic growth, renewable energy consumption, financial development, and the digital economy in shaping environmental sustainability, measured by the Load Capacity Factor (LCF), in European Union countries. Given the increasing policy focus on green transition and digital transformation, understanding both direct and interactive effects of these factors have become essential. Using panel data for EU countries over the period 2010-2025, the study applies the Method of Moments Quantile Regression (MMQR) to capture heterogeneous effects across different levels of environmental performance. The findings indicate that economic growth exerts a negative effect on environmental sustainability, while renewable energy consumption and financial development contribute positively, particularly at higher quantiles. The digital economy also shows a significant positive impact across the distribution of LCF. Importantly, the interaction results reveal that digitalization mitigates the environmental cost of economic growth and strengthens the beneficial effects of renewable energy and financial development. These findings highlight the pivotal role of the digital economy as both a direct and moderating driver of sustainability. Therefore, policymakers should integrate digital transformation strategies with renewable energy expansion and green financial systems to enhance environmental performance across EU countries.